Rapid Synthesis: Identifying Tax Benefits or Incentives to Reduce Poverty Among Older Adults - Mattison, CA; Gauvin, François-Pierre; Wilson, MG (My University, 2018)
An assessment of what is known about the tax benefits or incentives to reduce poverty among older adults. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum's Rapid Response program.
Keywords: tax; benefits; incentives; poverty; older